2021
DOI: 10.1021/acsami.1c14591
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Modification during Chemical Vapor Deposition of hBN on Sapphire

Abstract: A comparison of hexagonal boron nitride (hBN) layers grown by chemical vapor deposition on C-plane (0001) versus A-plane (112̅ 0) sapphire (α-Al 2 O 3 ) substrate is reported. The high deposition temperature (>1200 °C) and hydrogen ambient used for hBN deposition on sapphire substantially alters the C-plane sapphire surface chemistry and leaves the top layer(s) oxygen deficient. The resulting surface morphology due to H 2 etching of C-plane sapphire is inhomogeneous with increased surface roughness which cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 55 publications
4
20
2
Order By: Relevance
“…Notably, a recent study on the surface properties of the substrate comparing h-BN growth using diborane (B₂H₆) on a-cut and c-cut Al 2 O 3 revealed the former to be less likely to modify under growth conditions in the absence of an AlN buffer layer. 21 It is noteworthy from this study that when B₂H₆, a carbon-free boron precursor, was used to deposit BN without nitridizing the surface, h-BN films were observed.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Notably, a recent study on the surface properties of the substrate comparing h-BN growth using diborane (B₂H₆) on a-cut and c-cut Al 2 O 3 revealed the former to be less likely to modify under growth conditions in the absence of an AlN buffer layer. 21 It is noteworthy from this study that when B₂H₆, a carbon-free boron precursor, was used to deposit BN without nitridizing the surface, h-BN films were observed.…”
Section: Introductionmentioning
confidence: 75%
“…These results agree with suggestions from a recent surface study of BN growth on a-cut Al 2 O 3 , which described it to be more suitable for the growth of h-BN. 21 The presence of AlN 0002 and AlN 0004 peaks on both c-cut and a-cut Al 2 O 3 evidently dictates the epitaxial r-BN film growth on these substrates. This is supported by previous studies that have shown that h-BN initially nucleates epitaxially followed by r-BN epitaxial film growth on AlN (0001) grown on c-cut sapphire.…”
Section: E Differences In Film Nucleation and Growthmentioning
confidence: 95%
See 2 more Smart Citations
“…These simulations are performed with 700 HBNH molecules at 2000 K at different stages along with the simulation with a corresponding initial real gas pressure of 73 bar. A recent experimental study by Bansal et al 35 employs similar temperatures to synthesize hBN on a sapphire substrate with B 2 H 6 /NH 3 as precursors. Their work suggests that the precursor species might undergo chemical reactions before reaching the substrate surface.…”
Section: Reaxff Reactive Molecular Dynamics Methodmentioning
confidence: 99%